Can Exergaming with the Xbox Kinect Meet Guidelines for Exercise Intensity? - Yang, Chie; Wickert, Z.; Roedel, S.; Berg, A.; Rothbauer, A. (My University, 2013)
Exergaming, a new form of video game, is being promoted as an alternative form of enjoyable exercise to increase physical activity. The purpose of this study was to determine if the Xbox Kinect "Your Shape Fitness Evolved 2012" can produce moderate to vigorous intensity levels (MVPA) according to the American College of Sports Medicine (ACSM) guidelines for physical activity.
Color poster with text, images, tables, and photographs.
Keywords: Exergaming; Exercise intensity; Posters